ISSUES OF ENSURING LEGALITY AND APPLYING ADMINISTRATIVE PROCEDURES IN THE PROVISION OF PUBLIC SERVICES IN UZBEKISTAN - Rakhmanov Zafarjon Zayniddinovich (Western European Studies, 2025)
This article analyzes the relevance of ensuring legality in the provision of public services, issues of applying administrative procedures in the provision of public services.. The opinions of scientists on ensuring legality and applying administrative procedures in the provision of public services were discussed. Proposals and comments on the problems of ensuring legality and applying administrative procedures in the provision of public services and their solutions are presented
Keywords: Public services, legality, citizens' rights, administrative procedures, law enforcement practice.